The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Only two genera of the cosmopolitan tribe Cephenniini are known to occur in the People's Republic of China: Cephennodes Reitter and Cephennomicrus Reitter. The former is species-rich and abundant, especially in subtropical and sub-Himalayan areas, and so far nearly 80 species have been recorded in China. Cephennomicrus is rare, and only two species have been found in this vast country, in the south-eastern province of Fujian. Two new species are reported to occur in Yunnan: Cephennomicrus yunnanicus sp. n. and C. andreasi sp. n.